CLOUD SERVICE AND SCADA-BASED WEB APPLICATION FOR MONITORING RENEWABLE ENERGY SYSTEMS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
A renewable energy monitoring web application to track, monitor, and analyze the performance of renewable energy systems such as wind is presented in this paper. The main goal of this application is to provide users with real-time information on the energy production and consumption of their renewable energy systems. The application is meant to provide meaningful and easy-to-understand data visualization to users. This requires the application to have appropriate graphs, charts, and tables to help users quickly analyze the data. The application uses supervisory control and data acquisition (SCADA) for data collection and system monitoring. Amazon Simple Storage Service (S3), offered by Amazon Web Services (AWS), is used for data storage, as the application must handle large amounts of data and users. With the increase in the number of users and data points, AWS S3 helps to scale up without any performance degradation. The proposed renewable energy management system aims to develop a renewable energy monitoring and analytics web application with a user-friendly dashboard.
Keywords: Renewable energy; Web application; Supervisory control; Data acquisition; Data Analytics; Data Visualization; Cloud storage service; Tracking and monitoring.